A case of idiopathic isolated hypoglossal nerve palsy in a Korean child - Ji Hoi Yoon; Kyung Lae Cho; Hae Jung Lee; Seo Hui Choi; Kyung Yul Lee; Sung Koo Kim; Jun Hwa Lee (Korean Pediatric Society, 2011)
Hypoglossal nerve palsy (HNP) is an uncommon neurological abnormality that can provoke characteristic clinical signs, including unilateral atrophy of the tongue musculature. We present the case of a healthy 11-year-old Korean male who was admitted to the outpatient department of our institution with acute onset dysarthria, tongue fasciculations, and right-sided tongue weakness upon awakening. His evaluation included a virology work-up, neck magnetic resonance imaging (MRI), brain MRI, and otorhinolaryngological physical examination; all tests were normal and showed no evidence of inflammation. Fifteen days after the onset of symptoms, the patient recovered completely. Herein, we report a case of idiopathic isolated HNP in a Korean male.